Floristic survey of the caatinga in areas with different grazing intensities, Pernambuco, Northeast Brazil - Almeida-Cortez, Jarcilene Silva de; Tavares, Fernanda Meira; Schulz, Katharina; Pereira, Rita de Cássia Araújo; Cierjacks, Arne (Journal of Environmental Analysis and Progress, 2016)
A floristic survey was conducted in eighteen areas in the municipalities of Itacuruba and Floresta, Pernambuco, northeast Brazil. The objective was to investigate if the species richness of terrestrial plant species of the Caatinga is affected by grazing intensity. Eighteen 20x20 m2 plot were established in areas of low grazing intensity (9), and areas with high grazing intensity (9). We recorded 136 species belonging to 97 genera and 43 families. The most species-rich families were Poaceae (14), Fabaceae (13), and Asteraceae (11). The most species-rich genera were Aristida (Poaceae), Sida (Malvaceae) and Ipomoea (Convolvulaceae). The number of species in each study area (Itacuruba and Floresta) varied according to the distribution of the precipitation, the soil types, the land-use history type and the actual land-use. Areas with a low grazing pressure show a higher species richness of plant species than areas with a higher grazing intensity